2007
DOI: 10.1002/jmv.20857
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of viruses associated with acute gastroenteritis in children hospitalized with diarrhea in Ho Chi Minh City, Vietnam

Abstract: A molecular epidemiological study on common diarrheal viruses was conducted in Ho Chi Minh City, Vietnam between October 2002 and September 2003. Fecal samples were collected from 1,010 hospitalized children with acute gastroenteritis. Those samples were screened for groups A, B, and C rotavirus, adenovirus, genogroups I and II norovirus (NoV), sapovirus (SaV), and human astrovirus (HAstV) by RT-multiplex PCR, and the positive specimens were characterized further by ELISA, nested PCR, or sequencing. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
77
4
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 48 publications
17
77
4
2
Order By: Relevance
“…The 26 HAstV-positive samples, for example, were isolated mainly from children with mixed infections (17 samples) and from nonhospitalized children (17 samples). These results remain in accordance with those of several other studies showing that this virus causes asymptomatic infections or mild forms of gastroenteritis which are treated at home (5,25,28). More surprising was the result regarding the incidence of Aichi virus monoinfections.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The 26 HAstV-positive samples, for example, were isolated mainly from children with mixed infections (17 samples) and from nonhospitalized children (17 samples). These results remain in accordance with those of several other studies showing that this virus causes asymptomatic infections or mild forms of gastroenteritis which are treated at home (5,25,28). More surprising was the result regarding the incidence of Aichi virus monoinfections.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in Chile, China, France, and Australia reported NoVs as the etiologic agent in 8 to 15% of children with moderate to severe gastroenteritis who either attended the outpatient clinic or were hospitalized (4,17,30). Other studies in Finland (31) and Germany (28) and recently in Vietnam (25) found NoV in 20% to 55% of stool samples, whereas the incidence of RV was found in 31% to 67% of stool samples. Moreover, by coupling fecal detection with serological testing, Parashar et al (34) found in Peruvian children under 5 years old an incidence of NoVs that reached 55%, a rate comparable to that seen with of RVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies found lower levels of disease severity in norovirus than in rotavirus gastroenteritis, and most of these were carried out in developed countries [7,[43][44][45][46][47]. In contrast, other studies found no significant differences between the severity of rotavirus and norovirus infections [48][49][50][51]. One such study was conducted by us in Tunisia, and we attributed the severity of the norovirus infection to a lack of medical care at home and the delay to hospitalization for children infected with norovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Esse resultado está de acordo com o observado em outros estudos conduzidos em vários países, os quais demonstram o predomínio do tipo 41 em relação ao 40 36,37,38,39 . O tipo 41 esteve presente em 32 de 37 amostras de HAdV de um estudo conduzido no Vietnã 40 ; além disso, representou 94,5% do total de amostras positivas na Tunísia 23 . Na Austrália, a frequência do tipo 41 aumentou bastante no período de 1981 a 1992, passando de 25% em 1981 até atingir 100% em 1992 41 .…”
Section: Estudosunclassified